2017
DOI: 10.1039/c6ra25182j
|View full text |Cite
|
Sign up to set email alerts
|

A polycaprolactone/fish collagen/alginate biocomposite supplemented with phlorotannin for hard tissue regeneration

Abstract: In tissue engineering, scaffolds have been widely studied for the purpose of regenerating damaged tissues or organs. Biocompatibility of materials, pore structure, and even growth factors are effective for enhancing cell growth and differentiation. In particular, mammalian collagen is biocompatible and hydrophilic, and provides good cell attachment due to interactions between Arg-Gly-Asp (RGD) domains and cell membranes. However, there have been some limitations on the use of mammalian collagen. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Tissue and bone engineering is a new biomedical area where the phlorotannins are recently being tested [321]. This area focuses on the regeneration of damaged tissues, bones, or organs where biomedical scaffolds, cells, and growth factors are combined to obtain success [322].…”
Section: Tissue and Bone Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue and bone engineering is a new biomedical area where the phlorotannins are recently being tested [321]. This area focuses on the regeneration of damaged tissues, bones, or organs where biomedical scaffolds, cells, and growth factors are combined to obtain success [322].…”
Section: Tissue and Bone Regenerationmentioning
confidence: 99%
“…A study by Im et al [321] demonstrated that the insertion of phlorotannins on the fish collagen/alginate biocomposite obtained a better result in the cell proliferation. In the in vitro assay, this new mixture showed better results in calcium deposition and osteogenesis, demonstrating that this product with phlorotannins is a potential biomaterial for the bone tissue growth.…”
Section: Tissue and Bone Regenerationmentioning
confidence: 99%
“…Biological materials with proper hydrophilicity would be more favorable for cell growth. 44,45 From Figure 2D, the WCA of pADM was about 65°, and the WCA of 8MA−pADM was not significantly different from that of pADM. However, with the increase of DMC dosage, the contact angle of the material gradually decreased, that is, the hydrophilicity gradually increased.…”
Section: Structure and Surface Morphology Analysismentioning
confidence: 91%
“…A biomedical scaffold should have a three-dimensional shape that is structurally and mechanically equivalent to the replaced tissue and should provide attractive sites for the injected cells to attach, proliferate and differentiate. Biocomposite scaffolds based on polycaprolactone supplemented with hydrophilic collagen extracted from fish skin and phlorotannins from brown algae exhibited marked calcium deposition and osteogenesis ability compared to the materials not including the polyphenols [ 180 ]. Micro-/nano-fibrous substrates were also widely used for tissue regeneration because of their similarities to extracellular matrix components and their high surface area, which facilitates cell attachment and proliferation.…”
Section: Main Applications Of Phenol-based Polymers In Food and Hementioning
confidence: 99%